Effect of Ocimum sanctum in Sodium fluoride (NaF) induced Fluorosis in Rats: A Study with Respect to Antioxidant Enzymes and Fluorosis Markers - Shanmugam, Kondeti Ramudu; Shanmugam, Bhasha; Siva, Mavulapati; Ravi, Sahukari; Reddy, Kesireddy Sathyavelu (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Fluoride contamination was observed in groundwater’s of India, Pakistan, China, Indonesia and several other countries. In India the states like Andhra Pradesh, Telangana, Rajasthan, Haryana etc are contaminated with fluoride. Approximately 68 million people are suffering from fluorosis in India. The current study was done to know the antioxidant effect, anti-fluorosis and free radical scavenging property of Ocimum sanctum (OS). Methods: Superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione (GSH), glutathione reductase (GR), glutathione-s-transferase (GST), catalase (CAT), malondialdehyde (MDA), alanine aminotransferase (AAT), alkaline phosphatase (ALKP), aspartate aminotransferase (AST) and flurosis markers phosphorus (P4) and calcium (Ca) are estimated in all groups. 1,1-diphenyl-2-picryl hydrazyl radical (DPPH), hydroxyl radical, hydrogen peroxide (H2O2), Gas chromatography–mass spectrometry (GC-MS) was analyzed in methanolic extract of Ocimum sanctum. Results: SOD, GR, GSH, GPx CAT, activities and Ca levels are decreased in sodium fluoride (NaF) intoxicated rats. Whereas MDA, ALKP AST, AAT, and P4 levels are increased in NaF rats. However, Ocimum phenolic fraction treatment normalized the antioxidant enzymes, hepatic markers and flurosis markers in NaF intoxicated rats. DPPH, H2O2 and hydroxyl radical of ocimum posses potent free radical scavenging activities. GC – MS studies of Ocimum sanctum showed the presence of many bioactive compounds like Caryophyllene oxide, 2-(2-Propenyl)-m-anisidine, 2H-Pyan-2-one, 5,6-Dihydro-4-(2-methyl-3-methylene- 1-buten-4-yl etc. Further, histopathological observations prove that ocimum protects the hepatic tissue from NaF intoxication. Conclusion: Our study proves that Ocimum sanctum phenolic fraction protects the hepatic tissue from Na F induced fluorosis in rats.
Keywords: Ocimum sanctum; Antioxidant Enzymes; Fluorosis markers; Liver markers; GC-MS analysis; Rats